Comparison of the insidence of toxoplasmosis in feature samples of house cats and market cats in Sidoarjo City - Zazabilla, Indira; Lukiyono, Yauwan Tobing; Santoso, Andreas Putro Ragil; Prayekti, Endah (Environmental and Toxicology Management, 2023)
To determine the comparison of toxoplasmosis in the feces of cats house and cats market in the Sidoarjo City. This method is a direct slide method using a direct preparation using a 2% Eosin solution. The principle of stool examination uses a direct method that uses a microscope to determine stool that is positive for Toxoplasmosis. The results of this research were obtained in the form of primary data, namely the results of a microscope examination. There were 16 fecal samples taken by purposive sampling in the Sidoarjo City. This research was conducted at the Parasitology Laboratory at Universitas Nahdlatul Ulama Surabaya, Surabaya. Cats are animals that are very popular as pets. Cats can transmit zoonotic diseases, namely toxoplasma, which is caused by the Toxoplasmosis parasite. Toxoplasmosis infection is an intracellular parasite from the group of protozoa which is an obligate parasite, where cats act as definitive hosts. Results on the incidence of Toxoplasmosis using feces samples from cats house and cats market found no Toxoplasmosis infection.